Development of a novel portable test device to measure the tribological behaviour of shoe interactions with tennis courts - Ura, D.; Carre, M. (Procedia Engineering, 2016)
The interaction between tennis player and court is a complex problem determined by parameters that can be broken down as: the range of player movements and loading (e.g. push-off and sliding); a variety of surfaces (e.g. clay, acrylic and grass) and different shoe properties (e.g. sole material and tread geometry). These combinations generate different levels of friction that relate to both playing performance and safety. This paper presents the observations, findings and design methodology of a mechanical portable device to improve the understanding of tennis shoe-court interactions and allow courts to be measured and monitored.